2020
DOI: 10.3168/jds.2019-16910
|View full text |Cite
|
Sign up to set email alerts
|

Increased autophagy mediates the adaptive mechanism of the mammary gland in dairy cows with hyperketonemia

Abstract: Hyperketonemia is a metabolic disease in dairy cows, associated with negative nutrition balance (NNB) induced by low dry matter intake (DMI) and increased nutrient requirements. Hyperketonemia could induce metabolic stress, which might indirectly affect mammary tissue. Autophagy is a highly conserved physiological process that results in the turnover of intracellular material, and is involved in maintaining cellular homeostasis under the challenge of metabolic stress induced by NNB. The aim of this study was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 56 publications
3
18
0
Order By: Relevance
“…In dairy cows, autophagy is altered during metabolic disorders in the transition period. Enhanced autophagic activity in the liver and mammary gland has been associated with response mechanisms to alleviate metabolic stress induced by mild fatty liver and hyperketonemia (Chen et al, 2020;Li et al, 2020). At least in nonruminants experiencing metabolic disorders associated with adipose tissue dysfunction, autophagy is stimulated by oxidative stress (Zhang et al, 2012;Mizunoe et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In dairy cows, autophagy is altered during metabolic disorders in the transition period. Enhanced autophagic activity in the liver and mammary gland has been associated with response mechanisms to alleviate metabolic stress induced by mild fatty liver and hyperketonemia (Chen et al, 2020;Li et al, 2020). At least in nonruminants experiencing metabolic disorders associated with adipose tissue dysfunction, autophagy is stimulated by oxidative stress (Zhang et al, 2012;Mizunoe et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical data show that fatty liver in cows often manifests as insulin resistance. Cows with type I ketosis often exhibit low insulin levels, and those with type II ketosis often exhibit high insulin levels with decreased insulin sensitivity ( 26 , 34 , 35 ). Therefore, specific liver regulation of the insulin signaling pathway is crucial to explaining the pathogenesis of cow ketosis and fatty liver.…”
Section: Discussionmentioning
confidence: 99%
“…In line with our results, Chen et al indicated that enhanced formation and degradation of autophagosomes were found in the liver of cows with mild fatty liver during the perinatal period [ 15 ]. Moreover, Li et al previously suggested that activation of autophagy and an increase in the number of autophagosomes were found in the mammary tissues of cows with hyperketonemia [ 30 ]. Overall, autophagy can actively participate in the process of recycling and remobilizing nutrients in cells that serves as an adaptive mechanism for NEB.…”
Section: Discussionmentioning
confidence: 99%